The model of tourist virtual community members engagement management - Stepaniuk, Krzysztof (Business: Theory and Practice, 2015)
Building numerous and active virtual tourist communities involved in the tourist brand, connected with product, attraction or travel destination is a significant challenge for a dynamic and competitive tourist market. The main aim of presented pilot study was the drawing up guidelines for development of users engagement of selected virtual tourist communities on the example of Facebook. For that purpose a ranking of the most popular indicators of thematic areas, around which virtual tourist communities are formed was built. Simultaneously a typology of members of virtual tourist communities was presented as well as motives for the participation in communities gathered around the definite subject matter were analysed.